Cover Image, Volume 77, Issue 12. Issue 12 (9th November 2021) - Peach, Daniel AH; Almond, Max; Ko, Elton; Meraj, Sanam; Gries, Regine; Gries, Gerhard
Abstract : The cover image is based on the Research Article Cheese and cheese infusions: ecological traps for mosquitoes and spotted wing Drosophila by Daniel AH Peach et al., https://doi.org/10.1002/ps.6603 . Image Credit: Sean McCann. Abstract : The cover image is based on the Research Article Cheese and cheese infusions: ecological traps for mosquitoes and spotted wing Drosophila by Daniel AH Peach et al., https://doi.org/10.1002/ps.6603 . Image Credit: Sean McCann.